Values education: university social responsibility (Praxis Educativa, 2024)
Universities are a formative scenario that transforms reality and their actions must go beyond commitment andcitizen solidarity. The objective of this review article is to present a study on the conceptualization, definition andeducation in values, and an analysis of the theoretical-methodological referents of University Social Responsibility.Systematic literature review and bibliometric analyses were carried out in the programs VOSviewer version 1.6.19and Connected Papers. The results show that strengthening the sense of identity and belonging of the competentprofessional committed to academic, economic, social and environmental actions, with respect to the place wherehe/she studies, lives and works, is fundamental to achieve transformations in order to improve the quality ofcitizenship education. In conclusion, it is necessary to continue stimulating the apprehension of the value ofuniversity social responsibility in higher education institutions.
Keywords: civic education, moral values, vocational training, social responsibility, universities.